Smart Cities and Socioeconomic Inequality: A Critical Perspective on Smart City Practices in Indonesia - Daimah, Daimah (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The rapid adoption of smart city initiatives in Indonesia reflects a national ambition to modernize urban governance through digital innovation. However, despite increasing investments in smart infrastructure, significant disparities in socio-economic outcomes remain prevalent. This paradox raises a critical question: Do smart cities in Indonesia truly enhance inclusivity, or do they reinforce existing inequalities? This study aims to critically examine the relationship between smart city implementation and social inequality in five major Indonesian cities: Jakarta, Bandung, Surabaya, Makassar, and Semarang. Using a convergent mixed-methods approach, the research integrates quantitative data analysis—including Smart City Index scores, Gini coefficients, and internet access rates—with qualitative critical discourse analysis (CDA) of policy documents and urban governance narratives. The findings reveal a consistent mismatch between technological advancement and social equity. Cities with high smart city performance often report elevated levels of income inequality, and digital infrastructure remains disproportionately concentrated in urban centers, excluding marginalized communities. Furthermore, policy discourses prioritize efficiency and modernization, while overlooking equity, participation, and redistribution. This study concludes that smart city strategies in Indonesia, as currently designed, risk deepening the digital and social divide. It calls for a redefinition of smart urbanism—one grounded in social justice, participatory governance, and inclusive policy design. Such a shift is essential to ensure that smart technologies genuinely serve all urban residents, not just the digitally privileged.